The contribution of internal audit to management of the organizations: The perspective of management entities - Lourenço, Pedro; Laureano, Raul M. S.; Laureano, L. (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
Currently we live in a context of great demand characterized by constant and rapid changes which create challenges to management entities. In these circumstances and considering the position occupied by internal auditing in the organization' s structure, this activity can play an important role by providing information, suggestions and recommendations to management entities so that they can make the informed decisions. Hence this research evaluates the contribution of internal audit to organization's management and identifies the organizational dynamics which influence that contribution using a sample of management entities of 25 large Portuguese companies. Results reveal an effective contribution of internal audit to organization's management and show as enhancers of this contribution: the involvement of organization in internal audit, internal audit and management interaction and independence granted to internal audit. Top managers must ensure a strategic alignment between management and internal audit to reflect benefits of this activity in decision-making process and to gain competitive advantages.